Enantioselective reactions catalyzed by phosphine oxides. Issue 33 (16th August 2019) - Ayad, Tahar; Gernet, Aurélie; Pirat, Jean-Luc; Virieux, David
Abstract: The development of chiral small organic molecules that serve as Lewis base catalysts promoting highly stereoselective transformations has been the subject of intense research over the past decades. As a matter of fact, among the plethora of molecules used as Lewis bases, chiral phosphine oxides have thoroughly been overlooked by the organic synthetic community. Thus, this review focuses exclusively on Lewis base catalysis mediated by chiral phosphine oxides with emphasis on mechanistic aspects, covering most of the publications related to this field since their first use as organocatalyst in 2005 until the end of March 2019. Graphical abstract: Image 1